Ruptured intracranial tubercular infectious aneurysm secondary to a tuberculoma and its endovascular management. (April 2013) - Saraf, R.; Limaye, U.
Abstract Tuberculosis remains to be an endemic infectious disease in developing countries. With the increasing incidence of HIV and AIDS, there is further increase in the incidence of tuberculosis. Although CNS involvement by tuberculosis is seen in all age groups, there is a predilection for younger patients. Central nervous system tuberculosis may present as tuberculoma, cerebral abscess or tuberculous meningitis (TBM). Vasculitis secondary to TBM can cause infarcts and rarely aneurysm formation. In TBM there is a thick, gelatinous exudate around the sylvian fissures, basal cisterns. There is a border zone reaction occurring in the surrounding brain tissue. Inflammatory changes occur in the vessel wall of the arteries bathed in the exudate leading to narrowing of the lumen or occlusion by thrombus formation. The vessels at the base of the brain are most severely affected, including the internal carotid artery, proximal middle cerebral artery and perforating vessels of the basal ganglion. In these cases, the infection probably spreads from the adventitia towards the internal elastic lamina, weakening the vessel wall, with subsequent formation of an infectious aneurysm. Intracranial tuberculomas are space-occupying masses of granulomatous tissue that result from haematogenous spread from a distant focus of tuberculous infection. In endemic regions, tuberculomas account for as many as 50% of all intracranial space-occupying lesions. Inflammation in the vessels surrounding the tuberculoma may lead to formation of aneurysms. This case report illustrates an unusual case of intracranial tuberculomas complicated by intralesional haemorrhage due to an infective tubercular aneurysm in its vicinity. The endovascular treatment of these infectious aneurysms is safe, effective and durable. To the best of our knowledge, this is the first case report of a tuberculoma having intracranial haemorrhage on anti-tubercular treatment due to an infectious aneurysm developing in an artery in the vicinity of the tuberculoma and managed end.